Reaction of potential guava rootstocks to Meloidogyne enterolobii - Chiamolera, Fernando Marcelo (2018)
ABSTRACT Root-knot nematode Meloidogyne enterolobii is the main phytosanitary problem of guava cultivation in Brazil. Among the strategies to manage the problem, the best prospects are in identifying or developing cultivars or rootstocks that are resistant to this nematode. To identify plants with potential as rootstocks for guava, the reaction of araçá (wild guava) to M. enterolobii was assessed in a greenhouse experiment. Seven araçá species were evaluated (Eugenia stipitata, Psidium acutangulum, P. cattleyanum ‘yellow’, P. friedrichsthalianum, P. guajava var. minor, P. guineense, and Psidium sp.). The plants were inoculated with a suspension of 3,000 eggs of M. enterolobii, using eggplant as control treatment. The parameters fresh root mass, number of eggs and second stage juveniles (J2) per root system, the reproduction factor (RF = Pf/Pi), and araçá reaction were determined during the experiment. RF of the araçá species E. stipitata, P. cattleyanum ‘yellow’, and P. friedrichsthalianum was less than one (RP < 1), therefore resistant to M. enterolobii. The araçá trees had good root system development and the susceptible plants showed many root galls, high number of eggs and J2, and Fusarium solani and Rhizoctonia solani root rot. The araçá species, P. cattleyanum ‘yellow’, P. friedrichsthalianum, and E. stipitata are resistant to M. enterolobii and can be tested as potential guava rootstocks.